(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic exerted major impacts on the entire population, but some groups such as sexual and gender minorities have been disproportionately affected. Therefore, we aim at assessing the impacts on the social life and mental health of Brazilian sexual and gender minorities during the COVID-19 pandemic. This is a cross-sectional nationwide study conducted between September and October 2020. Participants were recruited through convenience sampling (snowball), being invited to answer an online questionnaire. The participants were invited to participate by social networks and websites directed to the LGBT+ population over 18 years old. This study included 659 sexual and gender minorities from all five Brazilian regions. The main impacts caused by the COVID-19 pandemic reported by the participants were anxiety (73.5%), stress (71%), loneliness (59.6%), sleep pattern changes (69%) and income reduction (36.9%). Participants with low educational level presented higher income reduction than participants with high educational level (0.61, 95% CI 0.48-0.77) and high income (0.46, 95% CI 0.34-0.62). Low income (1.14, 95% CI 1.03-1.26) and being lesbian (1.13, 95% CI 1.01-1.26) are related to changes in sleep patterns. Totally isolated participants presented high stress rates. The LGBT+ population presented high economic and emotional impacts during COVID-19 pandemic. The results of this study highlight the need for heath public policies directed for sexual and gender minorities.